Influência de metodologias de inoculação de Macrophomina phaseolina no desempenho de cultivares de soja - Cruciol, Giovana Carolina Dourado [UNESP] (2018)
Charcoal rot caused by the fungus Macrophomina phaseolina is one of the major diseases that causes rot in the root system and stem of soybean plants, and its occurrence has increased at every harvest season. The aim of this study was to evaluate the influence of M. phaseolina inoculation methodologies on the performance of soybean cultivars. The experiment was conducted in a completely randomized design, in sub-subdivided plots, containing two soybean cultivars (NA 7337 RR and CD 2737 RR), six inoculation methods (non-inoculated seed, seed inoculated for 48 hours, seed inoculated for 72 hours, soil infestation with three rice grains, soil infestation with six rice grains and soil infestation with nine rice grains) and three evaluation periods (20, 40 and 60 days after sowing) with 6 replicates. Evaluations were performed by measuring the height of plants, diameter of the colon, number of leaves, length and width of leaves and incidence of the fungus Macrophomina phaseolina. Results of the experiments indicated that the inoculation method using rice grains inoculated with the fungus M. phaseolina provided greater damage to the cultivar NA 7337 RR, but the cultivar CD 2737 RR was influenced by the method of inoculating directly in the soybean seed. The cultivar NA 7337 RR showed to be more tolerant to the fungus Macrophomina phaseolina. In the evaluation periods, the indirect quantification parameters of the disease progressively evolved at 20, 40 and 60 days. Only control treatment did not present the fungus M. phaseolina and all employed inoculation methods provided the development of the fungus in soybean plants. All inoculation methods were efficient in inoculating M. phaseolina in soybean plants. The method of directly inoculating in the seed for 48 and 72 hours developed early symptoms